Factors influencing uptake of HPV vaccination among girls in Germany - Stefanie Schülein; Katherine J. Taylor; Jochem König; Matthias Claus; Maria Blettner; Stefanie J. Klug (BMC, 2016)
Abstract Background Adequate coverage is key to the success of human papillomavirus (HPV) vaccination programmes. There is currently no organised HPV vaccination programme in Germany. The aim of this analysis was to determine HPV vaccine uptake as well as factors associated with uptake in nine to 17 year-old girls in Germany during the first year of vaccine availability. Methods This analysis is based on data from the Healthcare Access Panel, an established population-based household panel consisting of 55 000 representative households in Germany who were contacted between September and October 2007. A total of 4 747 households included at least one girl aged nine to 17 years. After reading a description of the HPV vaccine, these girls were asked, "Would you have yourself vaccinated against HPV?" Logistic regression analyses were performed to investigate associations between vaccination status and socio-demographic characteristics of the girls and their mothers. Results Of the 4 747 girls in the households who received questionnaires, 2 224 (46.9 %) participated in the study and 1 906 (40.2 %) answered the vaccination question. A total of 17.4 % of the girls were already vaccinated, 61.5 % felt positively about doing so, 4.7 % said they would not be vaccinated, and 16.3 % were not sure. The probability of a girl being vaccinated increased with each additional year of age (Odds Ratio (OR): 1.6, 95 % Confidence Interval (CI) 1.5-1.7). Among the 17 year-old girls, 38.5 % (95 % CI 32.6-44.4 %) had been vaccinated. Having a mother with high education (OR: 1.5, 95 % CI 1.0-2.3) or medium education (OR: 1.5, 95 % CI 1.1-2.1) versus basic education was a significant predictor for having been vaccinated. Similarly, medium (OR: 1.5, 95 % CI 1.0-2.4) versus low SES was significantly associated with having been vaccinated. Our analysis showed that during the first year of HPV vaccine availability in Germany, vaccination uptake was low. Conclusions Countries with organised HPV vaccination programmes showed much higher vaccination uptake, even in the first year after programme introduction. If vaccination uptake in Germany is to significantly improve in the future, an organised vaccination programme will need to be introduced.